“El dibujo como desarrollo de la creatividad”. - Laverde Anchatipan, Pamela Abigail (2024)
The current study examined the educational value of sketching as a didactic technique for fostering children's creativity. The objective was to enhance the use of sketching in the development of creativity of the students of the fifth year of EGB of the Dr. “Antonio Ante” School of the Canton Pujilí, Province of Cotopaxi, in the school year 2023 - 2024, the research was framed in the qualitative approach, inductive method, combining bibliographic and field research; for data collection we used the interview and observation techniques with their instruments, and an interview guide and observation guide applied to teachers and students. Based on the lack of resources at the institution to support creativity through drawing, the results showed that using sketching as a strategy to stimulate creativity is not frequently employed, nor are creative sketching techniques applied. Consequently, a proposal called “Guide to Activities to Promote the Sketch as a Didactic Strategy in the Development of Creativity”, which consists of seven activities where various sketch techniques are proposed to promote innovative learning experiences; with the application of this proposal, a higher level of motivation, sensitivity, innovation, participation, and freedom of students was obtained, which contributes to developing creative thinking skills.